The Effect of Capital Structure, Profitability and Audit Quality on Company Value with Company Size as a Moderation Variable - Zahrani, Kamilia; Mappadang, Agoestina; Mappadang, Jusuf Luther (International Journal of Asian Business and Management, 2023)
This study aims to analyze and examine the effect of capital structure, profitability, and audit quality on firm value with firm size as a moderating variable. From several populations of IDX indexed companies in the consumer goods industry sector, from the period 2017 to 2021, 64 companies were taken according to the criteria as samples. This research uses multiple regression analysis to measure the relationship between one variable and another. It was concluded that the research results show that capital structure and profitability can have an impact on company value. Unlike the case with audit quality indicators, it is known that they have no effect on company value. Another factor that can strengthen the profitability relationship is that it depends on the size of the company on the value of the company. On the other hand, company size is also able to weaken the relationship between capital structure and audit quality on company value